Exploring the Unseen: A Collective Emotional Framework in Entrepreneurial Orientation and Business Model Innovation - Kocoglu, Ipek; Imamoglu, Salih Zeki; Akgun, Ali Ekber; Ince, Huseyin; Keskin, Halit (Elsevier Science Bv, 2015)
Prevailing perspectives on entrepreneurial orientation (EO) and business model innovation (BMI) are mainly cognitive which hides the value of collective emotional framework in the creation of value through business innovation and entrepreneurial behavior patterns at the firm level reflecting risk-taking, innovativeness, proactiveness, competitive aggressiveness, and autonomy. This research aims to recognize the role of organizational emotional capability (OEC) as an organization-level affective mechanism, by integrating three theories; affective events theory, intergroup emotions theory and affect infusion theory. Subsequent to the development of an integrative, organization-level framework, the relationship between OEC, EO and BMI are empirically tested by investigating 207 firms located in Istanbul. Specifically we found that OEC, provides a pertinent environment as well as characteristics for the organization leveraging the entrepreneurial orientation and business model innovations in organizations through establishing a collective identity, and emotional attachment. We then discuss the results and future research opportunities. (C) 2015 Published by Elsevier Ltd.
11th International Strategic Management Conference -- JUL 23-25, 2015 -- Vienna, AUSTRIA
Keywords: Organizational emotional capability; entrepreneurial orientation; business model innovation